MDM2 SNP309 does not confer an increased risk to oral squamous cell carcinoma but may modulate the age of disease onset - Hamid, S.; Yang, Y.H.; Peng, K.N.L.; Ismail, S.M.; Zain, R.B.; Lim, K.P.; Wan Mustafa, W.M.; Abraham, M.T.; Teo, S.H.; Cheong, S.C. (Elsevier, 2009)
The MDM2 SNP309 has been associated with increased expression of the protein which could suppress p53 function, and has been shown to modulate risk to cancer. We have previously shown that overexpression of MDM2 is a common event in oral cancers. In the present study, we determined the association between the MDM2 SNP309 polymorphism and oral cancer in 207 oral cancer patients and 116 normal subjects. We genotyped the MDM2 SNP309 by PCR-RFLP. Logistic regression was adapted to calculate odds ratios for MDM2 SNP309 polymorphism from univariate and multivariable adjusted models. Our results suggest that MDM2 SNP309 does not confer increased risk to oral cancer (OR = 1.55, 95% CI = 0.77-3.11). However, the GG/TG genotype was associated with later disease onset in women above 55 years of age. Collectively, our data suggests that MDM2 SNP309 may modulate the risk to oral cancer and is a modifier of the age at oral cancer onset in women above the age of 55 years.